O desabrochar das mulheres: o feminino no alto desempenho em organizações empresariais privadas - Chu, Raissa Alves (2012)
This work aims to investigate how are sustained the desires and intimacies of women who are responsible for their families and their children education and, nowadays are also responsible for business conducting in large enterprises in São Paulo. It seeks to understand the implications of business life in the intimacy of women, including their desires and pleasures. This objective is justified by the curiosity to understand how these women lead their personal lives at the same time as professional life, in a culture permeated by general male characteristics. Is it necessary to waive any behavior perceived as feminine to achieve positions of great responsibility? How they deal with a culture of increasing performance demand and (seemingly) endless? How they feel about their own families? To answer these questions, a diverse literature was used, since it passes through different academic areas Administration, Sociology, Psychology. In addition, interviews were conducted for the purpose of this study to become more complete and true to life. The results were enlightening, revealing and presenting a paradox that perhaps today is not so explicit to the women themselves, since they face the challenge of their own performing careers